A Glimpse of Freedom: Allied Occupation and Political Resistance in East Germany - Luis R. Martínez; Jonas Jessen; Guo Xu (Institute of Labor Economics (IZA), 2022)
This paper exploits the idiosyncratic line of contact separating Allied and Soviet troops within East Germany at the end of WWII to study political resistance in a non-democracy. When Nazi Germany surrendered, 40% of what would become the authoritarian German Democratic Republic was initially under Allied control but was ceded to Soviet control less than two months later. Brief Allied exposure increased protests during the major 1953 uprising. We use novel data on the appointment of local mayors and a retrospective survey to argue that even a "glimpse of freedom" can foster civilian opposition to dictatorship.
Keywords: F51; H10; N44; P20; 330; spatial RDD; autocracy; protest; political resistance; East Germany; World War II